Lima’s newspaper and the defense of woman’s rights in the twentieth century - Mendoza Michilot, María (2016)
The role of women as leading actor of social change has been shown from various perspec- tives and approaches in newspapers, literary magazines and/or cultural newspapers in Latin America during the twentieth century. This study analyzes how the newspaper article perpe- tuates the social, cultural values as well as the social capital of women and their involvement as an active member of civil society and politics. Historically, the press has contributed to women for entering the public sphere allowing them to participate actively in the life of their nations. In Peru though; print journalism placed women in the political map however not with the deserved equity and justice. This research shows that, with few exceptions, major newspa- pers of Lima echoed the voices in adverse contexts for women to exercise their rights to elect and be elected. From a historical, communicative and sociological perspective the analysis of the contents shows what was said on that right and how they contributed to the recognition of citizenship of women in the establishment of women’s suffrage, which were granted only fifty years ago.